2021
DOI: 10.1136/bmjopen-2020-040718
|View full text |Cite
|
Sign up to set email alerts
|

The timing of continuous renal replacement therapy initiation in sepsis-associated acute kidney injury in the intensive care unit: the CRTSAKI Study (Continuous RRT Timing in Sepsis-associated AKI in ICU): study protocol for a multicentre, randomised controlled trial

Abstract: IntroductionAcute kidney injury (AKI) is one of the most common organ dysfunction in sepsis, and increases the risk of unfavourable outcomes. Renal replacement therapy (RRT) is the predominant treatment for sepsis-associated AKI (SAKI). However, to date, no prospective randomised study has adequately addressed whether initiating RRT earlier will attenuate renal injury and improve the outcome of sepsis. The objective of the trial is to compare the early strategy with delayed strategy on the outcomes in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
0
8
0
2
Order By: Relevance
“…Of the latest RCTs focused on the timing of initiation of KRT in critically ill AKI patients [137][138][139] , the IDEAL-ICU study 140 is the only one that focused on SA-AKI and demonstrated that earlier initiation of KRT had no significant survival benefit compared with 'standard' initiation, although a significant number of patients in the 'delayed' group were not treated with KRT, owing to spontaneous kidney recovery. Of note, a further study on the initiation of KRT in SA-AKI is currently underway 141 . Initiation of KRT in both septic and non-septic conditions should be based on clinical assessment and goals of EBP for kidney support, not just on creatinine levels and oliguria 69 .…”
Section: Extracorporeal Therapies For Sa-akimentioning
confidence: 99%
“…Of the latest RCTs focused on the timing of initiation of KRT in critically ill AKI patients [137][138][139] , the IDEAL-ICU study 140 is the only one that focused on SA-AKI and demonstrated that earlier initiation of KRT had no significant survival benefit compared with 'standard' initiation, although a significant number of patients in the 'delayed' group were not treated with KRT, owing to spontaneous kidney recovery. Of note, a further study on the initiation of KRT in SA-AKI is currently underway 141 . Initiation of KRT in both septic and non-septic conditions should be based on clinical assessment and goals of EBP for kidney support, not just on creatinine levels and oliguria 69 .…”
Section: Extracorporeal Therapies For Sa-akimentioning
confidence: 99%
“…It is highlighted that 27.23% evolved to death during the in-hospital period and 14.36% after discharge, which confirms the severity evidenced by the Charlson Comorbidity Index. It is also noteworthy that, even if it is a treatment, RRT has been pointed out as an independent risk factor for mortality during hospitalization [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other patients may have allergic reactions to the dialyzer or dialysis water, and hypotension in hypertensive patients may occur. For patients with late hemodialysis, dialysis-related amyloidosis may occur [ 19 , 20 ]. Long-term dialysis patients are prone to gastrointestinal bleeding, cerebral hemorrhage, etc.…”
Section: Discussionmentioning
confidence: 99%